Nieśmiertelność genetyczna. Hipoteza czy teoria? - Szyszko-Bohusz, Andrzej (1934- ) (Poznań: Wydawnictwo Naukowe Polskiego Towarzystwa Pedagogicznego)
In his publications author claims the notion of heredity can be understood as continuity of the parents' life in children. Theorefore, the chain of life and consciousness has been not interrupted despite of the death of an individual. The author states the Hypothes is of Genetic Immortality transforms novodays into Theory of Genetic Immortality (TGI).
Keywords: hypothesis; theory; genetic immortality; consciousness; genetic memory; personal identity; heredity; life; death; hipoteza; teoria; pamięć genetyczna; życie; Śmierć